Using the TROPOMI sensor to detect atmospheric pollutants originating from forest fires moving towards southern Brazil - Pasquetti , Luana; Schmitz , Guilherme Peterle; Neckel , Alcindo; Silva, Caliane Christie Oliveira de Almeida; Cardoso , Grace Tibério (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective - The general objective of this study is to quantify air pollution in the State of Rio Grande do Sul (Brazil), during the period from January 2021 to September 2024. Methodology - The quantitative qualitative method was used, combining environmental analysis and Remote Sensing in relation to the availability of images, using the Sentinel-5P satellite coupled to the TROPOspheric Monitoring Instrument (TROPOMI) under the domain of the European Space Agency (ESA) to analyze atmospheric pollutants. As well as the processing of the images collected using the SNAP (Sentinel Application Platform) and QGIS (Quantum GIS) software, in addition to the generation of data sheets applied to the K-means clustering methodology in the JASP software (version 0.18.3.0). Originality/relevance - to contribute to the creation of public environmental policies aimed at mitigating atmospheric pollution levels. Results - The results show that CO levels of 0.0244 mol/m² on September 11, 2024 were ≈5.9 times (490.16%) higher than normal average levels. NO2 levels in 2024 reached a value of 1.11E-5 mol/m², giving rise to levels ≈6.65 times (565.76%) higher than the average levels recorded. Theoretical/methodological contributions - This study contributes theoretically by deepening our understanding of the application of remote sensing techniques in the analysis of atmospheric pollution on a regional scale. Methodologically, it stands out for its integration of different analytical and computational tools - such as the joint use of SNAP, QGIS and JASP software - and for its adoption of the K-means clustering algorithm as a statistical technique for interpreting environmental data. This interdisciplinary approach offers a replicable environmental monitoring model that can be adapted to other regions and study contexts. Social and environmental contributions - the study provides concrete, up-to-date data on the levels of atmospheric pollutants in the state of Rio Grande do Sul, strengthening the scientific basis needed to formulate public environmental policies. By highlighting critical pollution peaks and their temporal variation, the research supports mitigation actions aimed at public health, emissions control and sustainable land management. It also stimulates awareness among the population and managers about the impacts of air pollution, promoting practices aimed at sustainable development.